Effectiveness and safety of interferon α2a as an add-on treatment for refractory Behçet's uveitis - Jing Shi; Chan Zhao; Jiaxin Zhou; Jinjing Liu; Li Wang; Fei Gao; Xiaofeng Zeng; Meifen Zhang; Wenjie Zheng (SAGE Publishing, 2019)
Objective: The objective of this study was to investigate the effectiveness and safety of interferon (IFN) α2a as an add-on treatment for refractory Behçet's uveitis (BU). Methods: In this retrospective cohort study, 30 refractory BU patients who received IFNα2a treatment in Peking Union Medical College Hospital between February 2015 and June 2018 were consecutively included. IFNα2a was used mainly as an add-on treatment for BU patients who underwent relapse under corticosteroids and conventional immunosuppressive agents. The primary outcome was treatment success rate before and after initiation of IFNα2a. Changes in ocular relapse rates, disease activity, corticosteroid- and immunosuppressant-sparing effects, as well as side effects were secondary outcomes. Results: A total of 30 patients (27 males and 3 females) with a mean age of 30.5 ± 8.7 years were included. Twenty-one patients (70%) were treated with at least 2 immunosuppressive agents before the initiation of IFNα2a. Treatment success was achieved in 26 patients (86.7%), and the median uveitis relapse rate decreased from 7.3 (range 2-12) to 0 (range 0-6) per patient-year ( p = 0.000002) during a mean follow-up of 21.7 ± 7.5 months, corticosteroids were lowered in 25 cases (83.3%) and completely withdrawn in four (13.3%). In addition, immunosuppressive agents were reduced in number and dosage in 22 (73.3%) and 29 patients (96.7%), respectively, and were completely withdrawn in 12 cases (40%). No severe adverse events were observed and serum autoantibodies remained negative during the treatment of IFNα2a. Conclusion: IFNα2a is effective and relatively safe in refractory BU, with significant steroid- and immunosuppressant-sparing effects.